2018
DOI: 10.1186/s13578-018-0253-z
|View full text |Cite
|
Sign up to set email alerts
|

EF-hand domain containing 2 (Efhc2) is crucial for distal segmentation of pronephros in zebrafish

Abstract: BackgroundThe blood filtering organ in zebrafish embryos is the pronephros, which consists of two functional nephrons. Segmentation of a nephron into different domains is essential for its function and is well conserved among vertebrates. Zebrafish has been extensively used as a model to understand nephron segmentation during development. Here, we have identified EF-hand domain containing 2 (Efhc2) as a novel component of genetic programme regulating nephron segmentation in zebrafish. Human EFHC2 is a protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“… SUPPORTING CITATIONS The following references appear in the Supplemental information : Austin-Tse et al (2013) ; Barrodia et al (2018) ; Chen et al (2020) ; Chiani et al (2019) ; Dougherty et al (2020) ; Gonsales et al (2020) ; Hirschner et al (2007) ; Huang et al (2020) ; Jerber et al (2014) ; Jungnickel et al (2018) ; Knowles et al (2013) ; Leslie et al (2020) ; Li et al (2020) ; Lorenzetti et al (2004) ; Reish et al (2016) ; Ryan et al (2018) ; Sasaki et al (2019) ; Shamseldin et al (2020) ; Silva et al (2016) ; Sun et al (2019) ; Suzuki et al (2009) ; Ta-Shma et al (2015) ; Ta-Shma et al (2018) ; Vogel et al (2010) ; Wilson et al (2010) ; Wu and Singaraja (2013) ; Xu et al (2015) ; Zhang et al (2019) . …”
mentioning
confidence: 99%
“… SUPPORTING CITATIONS The following references appear in the Supplemental information : Austin-Tse et al (2013) ; Barrodia et al (2018) ; Chen et al (2020) ; Chiani et al (2019) ; Dougherty et al (2020) ; Gonsales et al (2020) ; Hirschner et al (2007) ; Huang et al (2020) ; Jerber et al (2014) ; Jungnickel et al (2018) ; Knowles et al (2013) ; Leslie et al (2020) ; Li et al (2020) ; Lorenzetti et al (2004) ; Reish et al (2016) ; Ryan et al (2018) ; Sasaki et al (2019) ; Shamseldin et al (2020) ; Silva et al (2016) ; Sun et al (2019) ; Suzuki et al (2009) ; Ta-Shma et al (2015) ; Ta-Shma et al (2018) ; Vogel et al (2010) ; Wilson et al (2010) ; Wu and Singaraja (2013) ; Xu et al (2015) ; Zhang et al (2019) . …”
mentioning
confidence: 99%
“…Indeed, we found that esrrγa deficiency resulted in a decreased MCC cell number [marked by odf3b (also known as cimap1b ), an established marker of terminally differentiated MCCs], and co-injection of esrrγa RNA was sufficient to rescue the splice-blocking morpholino ( Fig. 1 I,J) ( Barrodia et al, 2018 ; Li et al, 2014 ; Liu et al, 2007 ; Xie et al, 2020 ). FISH analysis of the PST domain (marked by the boundaries of trpm7 ) also revealed a shift towards a transporter cell identity ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…We have shown that the EF-hand domain containing 2 (efhc2) knockdown results in expansion of distal early segments and reduction in CS and distal late segment. The expression of odf3, which marks multiciliated cells of pronephric tubules, was also reduced in efhc2 morphants (Barrodia et al, 2018).…”
Section: Identification Of Pronephros Segmentation Defectsmentioning
confidence: 96%
“…Defects in cilia present in zebrafish pronephros often lead to body curling, cyst formation and tubule dilation (Sullivan-Brown et al, 2008). Multiciliated cells present in zebrafish pronephros can be visualized by WISH or fluorescence in situ hybridization (FISH) using antisense odf3b or rfx2 riboprobes (Liu et al, 2007;Barrodia et al, 2018). Cilia in zebrafish embryos can be stained using a-acetylated tubulin and g-tubulin can be used to mark the basal bodies (Jaffe et al, 2010;Zaghloul and Katsanis 2011).…”
Section: Pronephric Cilia Staining and Imagingmentioning
confidence: 99%